Immunotherapy for the Treatment of Breast Cancer: Emerging New Data - Mina LA (Dove Medical Press, 2020)
Lida A Mina,1 Shannon Lim,2 Shakeela W Bahadur,1 Abdul T Firoz3 1Hematology Oncology Department, Banner MD Anderson Cancer Center, Gilbert, AZ, USA; 2Pharmacy Department, Banner MD Anderson Cancer Center, Gilbert, AZ, USA; 3Science Department, Arizona State University, Tempe, AZ, USACorrespondence: Lida A MinaBanner MD Anderson Cancer Center, Suite 400, 2946 E Banner Gateway Dr, Gilbert, AZ 85234, USATel +1 480 256 3676Fax +1 480 256 4624Email Lida.mina@bannerhealth.comAbstract: Breast cancer is the most common type of cancer affecting women in the United States. Triple-negative breast cancer remains the most aggressive molecular subtype secondary to a lack of therapeutic targets. The search for a target has led us to investigate immunotherapeutic agents. Immunotherapy has recently demonstrated significant breakthroughs in various types of cancers that are refractory to traditional therapies including melanoma and Non-Small Cell Lung Cancer (NSCLC). Breast cancer however remains one of the tumors that was initially least investigated because of being considered to have a low immunogenic potential and a low mutational load. Over the past few years, antiPD1/PDL1 drugs have started to make progress in the triple-negative subtype with more promising outcomes. In this report, we review the treatment of triple-negative breast cancer and specifically shed light on advances in immunotherapy and newly approved drugs in this challenging disease.Keywords: breast cancer, immunotherapy, PD1, PDL1, atezolizumab